PENERAPAN LEARNING ORGANIZATION PADA BADAN PENGAWASAN KEUANGAN DAN PEMBANGUNAN (BPKP) PERWAKILAN PROVINSI RIAU - Melisa Eka Putri; Zulkarnaini " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Learning organization is an organization that with all its strengths, together and continuously transforms itself to be better able to collect, manage and use knowledge for the success of the company or organization. The Finance and Development Supervisory Agency (BPKP) of the Riau Province Representative is one of the pioneers of the government in the field of supervision that continues to improve its quality. Increased employee competency in BPKP Riau Province has carried out the learning process through two main programs, namely: Independent Training Program (PPM) in its own office and Education and Training (Training and Education) at the BPKP Training Center. As for the purpose of this study is to analyze the application of learning organizations in Finance and Development Supervisory Agency (BPKP) Representative Province of Riau and the factors that hinder it. The theory used is the theory of Peter M. Senge namely there are five indicators that determine the learning organization in an organization; Systems thinking; Personal Expertise; Mental Model; Joint Vision; and Team Learning. This study uses a qualitative research with a descriptive approach and the data required for both primary and secondary obtained through interview, observation and documentation techniques for further analysis using triangulation data analysis techniques. The results of this study indicate that: first, the Implementation of Learning Organization in BPKP Representatives of Riau Province has been carried out only with functional learning types. Second, the factors that hinder the Implementation of Learning Organization in BPKP, namely: There has not been a recent innovation of learning methods, time, and internal factors of employees.Keywords: Learning Organization,  Implementation